Analysis of the Yellow Bean Corridor in Tanzania - Birachi, Eliud Abucheli; Sperling, L.; Kadege, E.; Mdachi, M.; Upendo, T.; Radegunda, Kessy; Mutua, Mercy M.; Mbiu, J.; Raya, N.; Ndunguru, A.; William, M.; Kabungo, C.; et al. (2021)
The yellow bean value chain in Tanzania was necessary to understand value chain. The objective of the survey was to characterize and explore trade of yellow bean grain and potential seed. The survey collected data and grain samples from 298 grain traders (including wholesalers, exporters, aggregators, and retailers) and 64 potential seed traders (large and retail traders) from 12 regions across four administrative zones in Tanzania. The grain samples collected were for DNA analyses. Results show existence of an established yellow bean corridor across Tanzania and the region at large (Burundi, DRC, Kenya, Rwanda, Uganda, Zambia) and demonstrated a huge market pull in the Eastern and Southern Africa regions. There are also strong perceptions on the organoleptic quality of various yellow bean grains and varieties that are traced to their sources.